Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.7554/elife.73208
|View full text |Cite
|
Sign up to set email alerts
|

Critical role for isoprenoids in apicoplast biogenesis by malaria parasites

Abstract: Isopentenyl pyrophosphate (IPP) is an essential metabolic output of the apicoplast organelle in Plasmodium falciparum malaria parasites and is required for prenylation-dependent vesicular trafficking and other cellular processes. We have elucidated a critical and previously uncharacterized role for IPP in apicoplast biogenesis. Inhibiting IPP synthesis blocks apicoplast elongation and inheritance by daughter merozoites, and apicoplast biogenesis is rescued by exogenous IPP and polyprenols. Knockout of the only… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 97 publications
(376 reference statements)
3
38
1
Order By: Relevance
“…The structural determination of the isolated species was checked via HRMS investigations. The fragmentation profiling by MS/MS confirmed the expected product ions at m / z 444 and m / z 119 related to the fragmentation of β-carotene as recently reported by Okada et al [ 33 ] (see Supplementary Material for details). More in detail, the fragment ion spectrum for the β-carotene standard and for the β-carotene isolated by HPLC are shown in Figures S1 and S2 , respectively.…”
Section: Resultssupporting
confidence: 86%
“…The structural determination of the isolated species was checked via HRMS investigations. The fragmentation profiling by MS/MS confirmed the expected product ions at m / z 444 and m / z 119 related to the fragmentation of β-carotene as recently reported by Okada et al [ 33 ] (see Supplementary Material for details). More in detail, the fragment ion spectrum for the β-carotene standard and for the β-carotene isolated by HPLC are shown in Figures S1 and S2 , respectively.…”
Section: Resultssupporting
confidence: 86%
“…The MEP pathway leads to the formation of isoprene units, isopentenyl pyrophosphate (IPP), and its isomer dimethylallyl pyrophosphate (DMAPP). Longer isoprenoid pyrophosphates are formed by polyprenyl synthases, which condense consecutively several isoprene units ( Okada et al, 2022 ; Tonhosolo et al, 2005 ). The simplest oligoprenyl pyrophosphates are geranyl pyrophosphate (10 carbon), farnesyl pyrophosphate (FPP, 15 carbon), and geranylgeranyl pyrophosphate (GGPP, 20 carbon) which are directly used for farnesylation and geranylgeranylation of proteins ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Reports in the literature indicate that FPP can also be used for the formation of Heme-O ( Simão-Gurge et al, 2019 ). The parasite also should produce longer prenyl pyrophosphates such as octaprenyl and nonaprenyl pyrophosphate (solanesyl pyrophosphate) necessary for the biosynthesis of ubiquinone, cis -polyprenols, and dolichols of 11, 12, and 15-19 isoprene units ( Okada et al, 2022 ; D'Alexandri et al, 2006 ; Zimbres et al, 2020 ; Verdaguer et al, 2021 ; Verdaguer et al, 2019 ). Finally, some authors previously suggested that the parasite can use phytol (POH) to synthesize vitamin E ( Sussmann et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…This confirms the importance of the apicoplast Fe-S cluster synthesis machinery for isoprenoid metabolism. In Plasmodium , interfering with apicoplast-hosted isoprenoid production affects the morphology of the organelle (70) but depletion of IspG and IspH does not lead to loss of the apicoplast (37), while interfering with the SUF pathway does (13). We also observe a late impact on the organelle (Fig.…”
Section: Discussionmentioning
confidence: 99%